Rancang Bangun Lms Berbasis Web Menggunakan Project-Based Learning Untuk Meningkatkan Kemampuan Berpikir Komputasional Pada Kompetensi Pemrograman Dasar - Ika Desy Pramita Sari; Muhammad Sonhaji Akbar (CV. SINAR HOWUHOWU, 2026)
The teaching and learning process of Algorithm and Programming in vocational high schools is still dominated by conventional teaching methods, resulting in low student engagement and underdeveloped computational thinking skills. This study aimed to develop and evaluate the feasibility and effectiveness of a web-based Learning Management System (LMS) implementing the Project-Based Learning (PjBL) model. The research employed the Research and Development (R&D) method using the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. The research subjects were 35 tenth-grade students of the Computer and Network Engineering (TKJ) program at SMKS Dharma Bahari Surabaya. Data were collected through expert validation, system testing, pretest-posttest, and project assessment, and were analyzed using descriptive statistics, the Wilcoxon Signed Rank Test, and N-Gain analysis. The results showed that the developed web-based LMS was categorized as highly valid based on expert evaluations. The Wilcoxon Signed Rank Test yielded an Asymp. Sig. (2-tailed) value of 0.000 (p < 0.05), while the N-Gain score of 0.6227 was classified as moderate. Therefore, the web-based LMS implementing the Project-Based Learning model was considered feasible and effective in improving students' computational thinking skills in basic programming competency.